2007
DOI: 10.1590/s0100-41582007000300007
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de isolados de Rhizoctonia spp. e identificação de novos grupos de anastomose em jardim clonal de eucalipto

Abstract: Espécies de Rhizoctonia causam queima foliar em brotações de jardim clonal e podridão de estacas durante o enraizamento, que podem limitar a clonagem do eucalipto, por estaquia. Diante da importância do patógeno para a cultura e da falta de estudos sobre a diversidade de isolados, esse trabalho objetivou caracterizar isolados e relatar novos grupos de anastomose de Rhizoctonia spp. em jardim clonal de eucalipto. Os isolados obtidos nas diferentes fases de propagação por estaquia foram caracterizados quanto ao … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(22 reference statements)
1
1
0
2
Order By: Relevance
“…Erper et al (2016) analyzing morphological characteristics of Rhizoctonia solani isolates belonging to the AG-4 anastomosis group found differences in both, colony color and sclerotia formation in PDA medium. We also observed color variability in our study as also observed by Sanfuentes et al (2007). Spedaletti et al (2016) showed that 62.9% of the colonies of Rhizoctonia solani grown in PDA had a light brown coloration and that only 20.6%…”
Section: Discussionsupporting
confidence: 86%
“…Erper et al (2016) analyzing morphological characteristics of Rhizoctonia solani isolates belonging to the AG-4 anastomosis group found differences in both, colony color and sclerotia formation in PDA medium. We also observed color variability in our study as also observed by Sanfuentes et al (2007). Spedaletti et al (2016) showed that 62.9% of the colonies of Rhizoctonia solani grown in PDA had a light brown coloration and that only 20.6%…”
Section: Discussionsupporting
confidence: 86%
“…In Brazil, the occurrence of binucleate Rhizoctonia of the AG-A and AG-R AG causing disease in potato (Solanum tuberosum L.) has also been reported (Inokuti et al, 2019); AG-A, AG-L, AG-O, AG-P in eucalyptus (Eucalyptus grandis W. Hill ex Maiden.) (Sanfuentes et al, 2007); AG-A, AG-F, AF-Fa, AG-G, AG-P and AG-R in common bean and corn (Blanco & Costa, 2018). Furthermore, there are reports of pathogenic binucleate Rhizoctonia in eucalyptus (Silveira et al, 2000), but AG were not mentioned.…”
Section: Treatment Srsi a Germination (%) Amentioning
confidence: 99%
“…y Rhizoctonia spp. Estas fueron transportadas al laboratorio de fitopatología de la Facultad de Ciencias Agrícolas de la Universidad de Córdoba, donde fueron lavadas, procesadas e incubadas en cámaras húmedas a 28°C por 72 horas (Sanfuentes et al, 2007). Se aislaron los géneros fungosos de Rhizoctonia spp.…”
Section: Obtención De Aislamientos De Rhizoctonia Spp Y Cylindrocladi...unclassified
“…Sin embargo, pese a la exitosa producción forestal, existen diferentes factores que ponen en riesgo el establecimiento de este sistema productivo, como lo son los problemas fitosanitarios tanto a nivel de campo como en vivero (Simeto et al, 2020). Algunos de los patógenos que tienen un impacto significativo en la etapa de vivero son Rhizoctonia solani Kühn, que causa tizón de las hojas y pudrición de esquejes durante el enraizamiento (Da Silveira et al, 2000;Sanfuentes et al, 2007), y Cylindrocladium spp. que es uno de los géneros fungosos con mayor presencia en viveros forestales, siendo responsable de la pudrición de estacas, tizón de las ramas, defoliación severa y la mortalidad de plántulas (dos Santos et al, 2021;Klinsukon et al, 2021).…”
Section: Introductionunclassified